Associations between objective and self-perceived physical activity and participation in everyday activities in mild stroke survivors - Cristina de Diego-Alonso; Jorge Alegre-Ayala; Julia Blasco-Abadía; Víctor Doménech-García; Pablo Bellosta-López (PLoS ONE, 2025)
Background and purpose Stroke survivors present limited levels of physical activity (PA) and participation in everyday activities although the specific interaction between PA and participation in these individuals is still uncertain. This study aimed to analyse the relationship between PA and participation in everyday activities among Spanish mild stroke survivors. Methods A total of 130 mild stroke survivors (61.3 ± 12.4 years, 35% female) with preserved walking ability and without cognitive and communication impairments participated in this cross-sectional study involving several rehabilitation centres from Spain. Self-reported levels of PA were reported by the International Physical Activity Questionnaire - short form (IPAQ-SF). Objective PA measures were monitored with the wristband Fitbit Inspire 2, recording the average steps/day and kilocalories/day. Participation and activity satisfaction levels were measured with the Satisfaction with Daily Occupations-Occupational Balance (SDO-OB) and participation retention through Activity Card Sort (ACS). Results ACS total score showed a weak correlation with self-reported PA (rho = 0.324) and moderate correlations with kilocalories/day and average steps/day (rho ≥ 0.581), while stronger correlations were found for the ACS subdomain of instrumental activities (rho ≥ 0.640) compared to the subdomains of leisure activities and social participation (rho ≤ 0.454). SDO-OB participation showed moderate correlations with kilocalories/day, and average steps/day (rho ≥ 0.647), and a weak correlation with self-reported PA (rho = 0.303). Weaker correlations were found for SDO-OB satisfaction with objective PA measures (rho = 0.407) and self-reported PA (rho = 0.254). Relationships between variables were explored by calculating Spearman correlation coefficients. Discussion and conclusions The objective and self-reported measures of PA in mild stroke survivors have a bilateral relationship with their current participation levels and the retained instrumental activities of daily living. However, the weaker correlations with leisure and social participation may suggest that promoting PA alone without integrating it into daily activities relevant to the stroke survivor may be insufficient to achieve comprehensive goals during rehabilitation programs.